2016
DOI: 10.1371/journal.pone.0164824
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Helicobacter pylori Eradication with the Occurrences of Chronic Kidney Diseases in Patients with Peptic Ulcer Diseases

Abstract: The association of Helicobacter pylori eradication with the occurrence of renal dysfunction in patients with peptic ulcer diseases is still unclear. This study aimed to clarify the relevance of H. pylori eradication to the occurrence of chronic kidney diseases in patients with peptic ulcer diseases. Data that were available from 2000–2011 were extracted from the National Health Insurance Research Database in Taiwan, and all patients with peptic ulcer diseases (n = 208 196) were screened for eligibility. We div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…The physician should not be afraid of the adverse effect of these anti- H. pylori drugs. Instead, they should be more motivated to eradicate H. pylori in patients with CKD considering the potential complications and mortality in these patients who suffer from PUB [ 13 , 14 ]. With respect to the dosage, Ehsani Ardakani et al reported that half-dose triple therapy with clarithromycin, amoxicillin, and omeprazole is as effective as full-dose triple therapy in patients with ESRD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physician should not be afraid of the adverse effect of these anti- H. pylori drugs. Instead, they should be more motivated to eradicate H. pylori in patients with CKD considering the potential complications and mortality in these patients who suffer from PUB [ 13 , 14 ]. With respect to the dosage, Ehsani Ardakani et al reported that half-dose triple therapy with clarithromycin, amoxicillin, and omeprazole is as effective as full-dose triple therapy in patients with ESRD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Taiwan National Health Insurance Research Database, although there is a lower H. pylori infection rate in patients with CKD (58.5%) and ESRD (56.2%) and PUD than in those with PUD without CKD (70.2%) [ 13 ], early H . pylori eradication (≤90 days) is highly suggested because it is associated with a protective role against the exacerbation of kidney malfunction and overall mortality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, it was reported that early HP eradication is beneficial to patients with HP infection to avoid the occurrence of chronic kidney diseases. [ 51 ] Since proteinuria in patients with MN is decreased after HP eradication,[ 52 ] we speculated that HP eradication may be useful for T2DM patients in an effort to reduce the risk of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection and eradication triple or quadruple therapy was defined as proton-pump inhibitor (PPI) or histamine type 2 receptor antagonists (H2RA) plus clarithromycin or metronidazole plus amoxicillin or tetracycline, with or without bismuth for 7–14 days. [ 20 , 21 ]…”
Section: Methodsmentioning
confidence: 99%